KESESUAIAN IKLIM TERHADAP PERTUMBUHAN TANAMAN THE CLIMATE SUITABILITY FOR PLANT'S GROWTH - Dewi, Nur Kusuma (MEDIAGRO, 2005)
This  studies  purposed  to  analyze  climate  classification which  is used  in  Indonesia  commonly  and  the  suitability  each  climate  type  for plant's  growth.  The  climate classification  can  be  made  by  using  only  one  climate  substance  or  more. The prominent  classifications in Indonesia are Schimdt ± Ferguson  system  and  Oldeman  system.  Schmidt ± Ferguson  classification  system  appropiate  to  wooded  plant / plantation  and  forest  growth,  while  Oldeman  system  appropiate  to  seasonal  plants   like  rice  or  dry  season  crops.  The  suitable  climate  is  one  of  the  optimal  production  determined   factors. Keywords  :  Schimdt = Ferguson,  Oldeman  ,  Wooded   plants,  Seasonal plants